Фасадні керамічні матеріали з використанням відходів паливно-енергетичної промисловості - Щукіна, Людмила Павлівна; Цовма, Віталій Віталійович; Міхеєнко (Ященко), Лариса Олександрівна (Львівський державний університет безпеки життєдіяльності, 2015)
Technology facade ceramics based on high-carbon coal flotation waste as a primary raw material has been developed. Technological content of carbon (3 %) and clay component (20 %) in the mixtures have been established.Technological parameters of manufacturing of ceramic materials have been determined: compaction pressure 110 ÷ 130 kg/cm², humidity of press-powder 9 mass %, firing temperature 970 ÷ 1030 °С.
Facade ceramic materials with using of fuel and energy industry wastes
Keywords: ресурсозбереження; безпека екологічна; кераміка будівельна; продукт органо-мінеральний; шихта; пресування